Effect of urea or coconut cake supplementation on nutrient intake and digestion of Bali cows maintained on tropical grass hay - Jelantik, I.G.N; Belli, H.L.L (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Three rumen cannulated Bali cows were fed basal diet consisting of about 2 kg DM of medium quality grass hay (CP = 7.47%) together with ad libitum amount of low quality grass hay (CP = 3.5%) (HH). In the supplemented rations, this basal ration was supplemented with isonitrogenous amount of urea (HU) or coconut cake (HC). The experimental was on design 3 x 3 latin square aiming to study effects of different source of nitrogen supplementation on the intake of poor quality hay (PQH), total diet, nutrients supply and nitrogen utilisation by the animals. Changes in rumen environment and dry matter and protein degradation after supplementation were also investigated. Neither urea or coconut cake (CC) supplementation increased hay intake but the total dry matter intake was significantly higher (P < 0.05) in HC than in HH and HU. Digestibility of EE, CHO and GE but not NDF were also improved with CC supplementation. In contrast, CC supplementation tended to depress CF apparent digestibility. Rumen pH was significantly elevated (P < 0.05) with urea but it was reduced (P < 0.05) with CC supplementation. Both supplements increased rumen ammonia concentration, while total as well as individual VFAs remained unaffected. Dry matter and NDF rumen degradability tended to increase with urea but not with CC supplementation. Supplementation with coconut cake markedly improved protein balance while it was unimproved with urea supplementation. Key Words: Bali Cows, Urea, Coconut Cake, Digestion